Transformation of Ahlus Sunnah wal Jamaah Values: Between Spiritual Sustainability and the Risk of Commodification - Masitah, Dewi; Kartiko, Ari (Pascasarjana Universitas KH. Abdul Chalim, 2024)
This research aims to look for differences and gaps to find research gaps with previous research. To achieve this goal, the researcher asked the following research questions: first, competition for truth claims and the spread of Ahlusunah wal Jamaah, NU elites and Salafi elites to compete for influence in their preaching to Pasuruan society; secondly, Santri and the community became a source of struggle for influence for the commodification of NU elites. and Salafi elites in the political, economic and educational areas. Questions in the research will be asked of those who really understand and comprehend the themes raised in this research. This type of research uses qualitative research, with Alfred Schutz's phenomenological approach. The data used is primary data or main data. The data obtained comes from interviews with NU and Salafi elites, as well as city residents, as well as information taken from NU and Salafi books. Plus, field notes resulting from the observation process. The main data source is individual interview transcripts with NU and Salafi elites. The results of the research show that the form of commodification of Ahlusunah wal Jamaah Salafi ideology focuses on da'wah, namely returning Islam to the Koran and Hadith and an Islam that is free from heresy, superstition and superstition. The Salafi preaching model is not oriented towards practical politics; it collaborates with the Pasuruan city government.